2015
DOI: 10.5966/sctm.2015-0139
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived Human Induced Pluripotent Stem Cells From Gingival Fibroblasts Composited With Defined Nanohydroxyapatite/Chitosan/Gelatin Porous Scaffolds as Potential Bone Graft Substitutes

Abstract: Human embryonic stem cells and adult stem cells have always been the cell source for bone tissue engineering. However, their limitations are obvious, including ethical concerns and/or a short lifespan. The use of human induced pluripotent stem cells (hiPSCs) could avoid these problems. Nanohydroxyapatite (nHA) is an important component of natural bone and bone tissue engineering scaffolds. However, its regulation on osteogenic differentiation with hiPSCs from human gingival fibroblasts (hGFs) is unknown. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 58 publications
(73 reference statements)
0
51
0
Order By: Relevance
“…; Ji et al . ), and could be induced by different cytokines to form cartilage and bone (Rutherford et al . ; Tang et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Ji et al . ), and could be induced by different cytokines to form cartilage and bone (Rutherford et al . ; Tang et al .…”
Section: Introductionmentioning
confidence: 99%
“…As an important component of the periodontium, the gingival tissue could be obtained from patients undergoing teeth extraction, thus the collection of gingival tissue was by convenience. It has been reported that HGFs have the potential of multi-directional differentiation Ji et al 2016), and could be induced by different cytokines to form cartilage and bone (Rutherford et al 2002;Tang et al 2011). However, the question about whether HGFs could be induced by pro-angiogenic factors to differentiate into endothelial-like cells is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…hiPSCs have been differentiated into OBs on 2D plastic and 3D CaP scaffolds7891011 and produced dense bone matrix on 3D decellurized bone scaffolds in a perfusion bioreactor12. OCs have been generated from hiPSCs on 2D plastic and on mineralized substrates by embryonic body (EB) formation13 and by co-culturing with stromal cells14.…”
mentioning
confidence: 99%
“…The use of GFP-labelled hESC-OPs would be extremely useful in noninvasive imaging of bone regeneration within three-dimensional (3D) in vitro scaffolds and in vivo animal models. Recently, several studies have produced bone-like matrix by seeding human PSCs on different 3D scaffolds [40–43] and using perfusion bioreactors [44, 45]. Jeon et al used a biomimetic approach to regenerate bone by 3D coculture of human PSC-derived osteoblasts and osteoclasts within a synthetic scaffolds [46].…”
Section: Discussionmentioning
confidence: 99%